2012
DOI: 10.1088/1748-0221/7/07/p07010
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing quantum-dot-doped liquid scintillator for applications to neutrino detectors

Abstract: Liquid scintillator detectors are widely used in modern neutrino studies. The unique optical properties of semiconducting nanocrystals, known as quantum dots, offer intriguing possibilities for improving standard liquid scintillator, especially when combined with new photodetection technology. Quantum dots also provide a means to dope scintillator with candidate isotopes for neutrinoless double beta decay searches. In this work, the first studies of the scintillation properties of quantum-dot-doped liquid scin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…Properties of candidate QD samples have been previously reported [9]. These results demonstrated that QDs are promising candidates which benefit further study.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Properties of candidate QD samples have been previously reported [9]. These results demonstrated that QDs are promising candidates which benefit further study.…”
Section: Introductionsupporting
confidence: 61%
“…The idea to do direction reconstruction of charged particles in liquid scintillators is described elsewhere [9, 15]. Here, we note that QDs provide an interesting possibility of tuning the scintillation light such that the emission is at shorter wavelengths.…”
Section: Requirements For Liquid Scintillatorsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, high-temperature superconductivity has been induced in Bi 2 Se 3 flakes and films by interfacing with a cuprate superconductor Bi 2 Sr 2 CaCu 2 O 8+δ (Wang et al, 2013.;Zareapour et al, 2012). Very recently, evidence for MZMs has been reported in the cores of magnetic vortices in a thin film of Bi 2 Te 3 grown on the surface of a conventional superconductor NbSe 2 (Xu et al, 2014). Using scanning tunneling spectroscopy some features consistent with the theoretical prediction for the Fu-Kane model (Chiu et al, 2011) have been observed.…”
Section: D Systemsmentioning
confidence: 74%
“…A very advanced study on colloidal quantum dots performance, as liquid scintillator in toluene, has been performed in ref [2] and compared to PPO. The spectrum from a 90 Sr beta source was measured with 20 mL of toluene, showing a reasonable signal yields for 1.5 g/L of quantum dots from different suppliers.…”
Section: Qds In Liquid Scintillatormentioning
confidence: 99%